Anesthetist‐Directed Sedation Favors Success of Advanced Endoscopic Procedures. (February 2017) - Buxbaum, James; Roth, Nitzan; Motamedi, Nima; Lee, Terrance; Leonor, Paul; Salem, Mark; Gibbs, Dolores; Vargo, John
Abstract : OBJECTIVES: Sedation is required to perform endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) given the duration and complexity of these advanced procedures. Sedation options include anesthetist‐directed sedation (ADS) vs. gastroenterologist‐directed sedation (GDS). Although ADS has been shown to shorten induction and recovery times, it is not established whether it impacts likelihood of procedure completion. Our aim was to assess whether ADS impacts the success of advanced endoscopy procedures. METHODS: We prospectively assessed the sedation strategy for patients undergoing ERCP and EUS between October 2010 and October 2013. Although assignment to ADS vs. GDS was not randomized, it was determined by day of the week. A sensitivity analysis using propensity score matching was used to model a randomized trial. The main outcome, procedure failure, was defined as an inability to satisfactorily complete the ERCP or EUS such that an additional endoscopic, radiographic, or surgical procedure was required. Failure was further categorized as failure due to inadequate sedation vs. technical problems. RESULTS: During the 3‐year study period, 60% of the 1, 171 procedures were carried out with GDS and 40% were carried out with ADS. Failed procedures occurred in 13.0% of GDS cases compared with 8.9% of ADS procedures (multivariate odds ratio (OR): 2.4 (95% confidence interval (CI): 1.5–3.6)).This was driven by a higher rate of sedation failures in the GDS group, 7.0%, than in the ADS group, 1.3% (multivariate OR: 7.8 (95% CI: 3.3–18.8)). There was no difference in technical success between the GDS and ADS groups (multivariate OR: 1.2 (95% CI: 0.7–1.9)). We were able to match 417 GDS cases to 417 ADS cases based on procedure type, indication, and propensity score. Analysis of the propensity score‐matched patients confirmed our findings of increased sedation failure (multivariate OR: 8.9 (95% CI: 2.5–32.1)) but not technical failure (multivariate OR: 1.2 (0.7–2.2)) in GDS compared with ADS procedures. Adverse events of sedation were rare in both groups. Failed ERCP in the GDS group resulted in a total of 93 additional days of hospitalization. We estimate that 67, 891 would have been saved if ADS had been used for all ERCP procedures. No statistically significant difference in EUS success was identified, although this sub‐analysis was limited by sample size. CONCLUSION: ADS improves the success of advanced endoscopic procedures. Its routine use may increase the quality and efficiency of these services.